The Enlightenment above national context: political economy in eighteenth-century Scotland and Naples - Robertson, J (Cambridge University Press, 1997)
It is now common to study the Enlightenment 'in national context', and in few cases has the approach been more fertile than in the study of the Scottish Enlightenment. The danger of this approach, however, is that it deflects attention from the international connections of the Enlightenment, fragmenting the movement as a whole. It is argued here that the Enlightenment is better understood as an intellectual movement which was both cosmopolitan and patriotic, and that this is particularly evident in its commitment to political economy, as the key to improving the human condition in this world. The argument is developed through a comparison of Scottish and Neopolitan political economy from the mid- to the later eighteenth century. Though set apart by very different economic circumstances, the Scots and Neopolitans had a common point of reference in French economic writings, and through these Hume's ideas in particular were transmitted to Naples. It was from within this common intellectual framework that the Scots and the Neopolitans elaborated their distinctive positions on the scope for free trade between nations. If Hume and Smith believed that poor countries such as Scotland would prosper through greater free trade, while Genovesi and Galiani argued that only by measures of protection could the abundant natural resources of the kingdom of Naples be harnessed to its benefit, their differences derived from shared premises, and a comparable fear of the inclination of the leading mercantile powers, Britain and France, to control trade to their sole advantage.